Tourism and community development the case of Aklan province - Ilin, Stacey; Necesito, Rence; Obsequio, Chola Rikka; Quisote, Felrose (2004)
This study is about Tourism and community Development : The Case of Aklan Province. The study was conducted for the purpose of investigating tourism and its effects in community development in the Province of Aklan. Specifically, the study attempted to answer the (1) The different tourist destinations and festivities in Aklan (2) The tourism contributions to the economic, social, political and environmental aspects in Aklan, and (3) The role of action the Department of tourism has taken to promote the tourism industry of Aklan. The investigation processes focus mainly on AKlan tourism and community development. One hundred twenty five (125) respondents were randomly selected to participate in the study which includes (1) local and foreign tourists, (2) tourism employees and (3) the general population. The primary techniques in data collection include the questionnaire and secondary data obtained from official sectoral documents. Descriptive statistics was used to analyze data generated by the study. Based from the findings, the consciousness and awareness of every Aklanon had been enriched not only by tourist attractions in the province but also various cultural and religious festivities that captivated tourist to come and visit the place. As analyzed, the people and the government are aware of the factors that affect community development and its role in the development process. The Department of Tourism plays a major role in the development of tourism in Aklan. The agency is cognizant of its responsibility and accountability in the promotion, monitoring, controlling, evaluating and taking the necessary measured to ensure the progress of tourism industry in Aklan.
Research Paper (Mgt 199 - Management Research) -- [Iloilo City : UPV-CM], March 2004.